Cellular magnetic resonance with iron oxide nanoparticles: long-term persistence of SPIO signal in the CNS after transplanted cell death. (2014) - Cianciaruso, Chiara; Pagani, Antonella; Martelli, Cristina; Bacigaluppi, Marco; Leonardo Squadrito, Mario; Lo Dico, Alessia; De Palma, Michele; Furlan, Roberto; Lucignani, Giovanni; Falini, Andrea; Biffi, Alessandra; Ottobrini, Luisa; et al.
Aim: To study the specificity of cellular MRI based on superparamagnetic iron oxide particles (SPIOs), especially within the CNS.Materials & methods: A microglial cell line was engineered for the expression of a suicide gene, the receptor of diphtheria toxin (DT), and two reporter genes, green fluorescent protein and luciferase, in order to induce, in a controlled manner, cell death and test it through bioluminescence. SPIO-labeled DT-sensitive and control DT-insensitive cells were transplanted into the brains of mice, which underwent serial MRI and bioluminescence studies before and up to 90 days after DT-induced cell death.Results: No variations in SPIO signal voids were detected along longitudinal monitoring in brain hemispheres transplanted with DT-sensitive cells. Ex vivo analyses showed persistence of iron nanoparticle deposits at transplantation sites.Conclusion: Due to the long-term persistence of signal after transplanted cell death, caution is advised when SPIOs are employed for cell tracking. Original submitted 27 January 2014; Revised submitted 18 April 2014